No, not that one it's not a chair - Gonzalez-Foerster, Dominique; Zahm, Olivier (Paris : Galerie 1900-2000, 1990)
Armleder, John M. ; Artschwager, Richard ; Belcher, Alan ; Bijl, Guillaume ; Bourget, Marie ; Cazal, Philippe ; Culbert, Bill ; Dwyer, Nancy ; Ganahl, Rainer ; Gonzalez-Foerster, Dominique ; Grünfeld, Thomas ; Kienholz, Edward ; Lavier, Bertrand ; Lawler, Louise ; Lum, Ken ; Noland, Cady ; Vilmouth, Jean-Luc
No, not that one it's not a chair, Galerie 1900-2000, Paris, 1990
kunstcatalogus